2020
DOI: 10.21203/rs.3.rs-67262/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Age-dependent Shift in the de Novo Proteome Accompanies Pathogenesis in an Alzheimer’s Disease Mouse Model

Abstract: Alzheimer’s disease (AD) is an age-related neurodegenerative disorder, however neuropathological changes begin years before memory impairment. Investigation of the early molecular abnormalities in AD might offer innovative opportunities to target memory impairment prior to onset. Decreased protein synthesis plays a fundamental role in AD, yet the consequences of this dysregulation for cellular function remain unknown. We hypothesize that alterations in the de novo proteome drive early metabolic alterations in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…In K3 mice mice 43 , AHA labelling of the whole brain proteome over 16 hours in 5 months old mice showed, similar to our findings, a large reduction in neuronal protein synthesis rates measured by FUNCAT 43 . Proteomics analysis showed reduced differentially expressed proteins related to OXPHOS complexes, the TCA cycle, microtubules and actin cytoskeleton, synaptic proteins and ribosomal proteins, confirmed in rTg4510 mice, again similar to our findings and to results from hippocampal slices from APP/PS1 mice 44 , examined by AHA labelling over 5 hours combined with SILAC (BONLAC) which again revealed changes in synapses, proteasome, lysosome, OXPHOS and ribosomal proteins 44 . A separate study in APP/PS1 mice, heavy labeled AHA hippocampal proteome showed similar changes 45 .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In K3 mice mice 43 , AHA labelling of the whole brain proteome over 16 hours in 5 months old mice showed, similar to our findings, a large reduction in neuronal protein synthesis rates measured by FUNCAT 43 . Proteomics analysis showed reduced differentially expressed proteins related to OXPHOS complexes, the TCA cycle, microtubules and actin cytoskeleton, synaptic proteins and ribosomal proteins, confirmed in rTg4510 mice, again similar to our findings and to results from hippocampal slices from APP/PS1 mice 44 , examined by AHA labelling over 5 hours combined with SILAC (BONLAC) which again revealed changes in synapses, proteasome, lysosome, OXPHOS and ribosomal proteins 44 . A separate study in APP/PS1 mice, heavy labeled AHA hippocampal proteome showed similar changes 45 .…”
Section: Discussionsupporting
confidence: 90%
“…Yet the precise nature and identity of these dysregulated proteins has only recently begun to be explored [43][44][45] and is an important focus for an increased understanding of the subcellular mechanisms and processes that lead to neuronal dysfunction and death.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations